2012
DOI: 10.1134/s1066362212020087
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Pu(IV) and Np(VI) with carbohydrazide in nitric acid solution

Abstract: The reduction of Pu(IV) and Np(VI) with carbohydrazide (NH 2 NH) 2 CO in 1-6 M HNO 3 solutions was studied. The Pu(IV) reduction is described by a first-order rate equation with respect to Pu(IV). At [HNO 3 ] ≥ 3 M, the reaction becomes reversible. The rate constants of the forward and reverse reactions were determined, and their activation energies were estimated. Neptunium(VI) is reduced to Np(V) at a high rate, whereas the subsequent reduction of Np(V) to Np(IV) is considerably slower and is catalyzed by F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…As it was found, an earlier [2] Np(IV) formation from the Np(V) was observed at [HNO3] ≥3 mol/l and relatively high concentration of CO(N2H3)2 (more than 0.2 mol/l).…”
Section: The Interaction Of the Np(vi) With Carbohydrazidesupporting
confidence: 53%
“…As it was found, an earlier [2] Np(IV) formation from the Np(V) was observed at [HNO3] ≥3 mol/l and relatively high concentration of CO(N2H3)2 (more than 0.2 mol/l).…”
Section: The Interaction Of the Np(vi) With Carbohydrazidesupporting
confidence: 53%
“…17,19,21−23 Volk et al reported that carbohydrazide can quickly reduce Np(VI) to Np(V), while it further reduces Np(V) to Np(IV) very slowly. 17 23 These works suggest that the slow reduction of Np(V) to Np(IV) by carbohydrazide is probably the higher energy barrier, which is kinetically hindered. Although the reaction of Np(VI) to Np(V) by carbohydrazide was investigated experimentally, their mechanism is still unclear, so it is essential to explore the reaction mechanism of Np(VI) to Np(V) by CO(N 2 H 3 ) 2 from the perspective of theory.…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested to remove Np from the SNF reprocessing process using advanced PUREX processes such as the Partitioning Conundrum Key (PARC) process and SUPERPUREX process . Some free-salt reductants such as hydroxyurea, , hydrazine, and their derivatives have been experimentally applied to reduce Np­(VI).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the more efficient separation of Np from U and Pu in the PUREX process is the reduction of Np(VI) to Np(V). Experimental results have been reported for several highly efficient and environment-friendly Np(VI) reductants, including oximes, [4][5][6] aldehydes, [7][8][9] hydroxylamine, [10][11][12][13][14] urea, 15,16 hydroxamic acid, [17][18][19][20] hydrazine, [21][22][23][24][25][26][27][28] and their derivatives. Acetaldoxime reduces Np(VI) to Np(V) only at less than 2 M nitric acid concentration and low temperature (308 K).…”
Section: Introductionmentioning
confidence: 99%